Official documents of the Summit process of the Americas. Vol. 2 : 1998-2000 (The Secretariat Washington, D.C.US, 2000)
Contains inter-American Ministerial declarations which, for the most part, have been concluded between the 34 nations of the Summit process in the two years since the Second Summit of the Americas was held in Santiago, Chile in 1998.
Keywords: REGIONAL COOPERATION